RANCANG BANGUN FIRING SYSTEM PADA AMUNISI BERBASIS ARDUINO MENGGUNAKAN RADIO FREQUENCY - Irani, Andryas Doni; Priyandoko , Gigih; Effendy, Dedi Usman (Program Studi Teknik Elektro - Fakultas Teknik - Universitas Widyagama Malang, 2024)
Currently, there is a growing demand for more sophisticated, efficient, and secure fire systems in military applications. The use of microcontroller technology and wireless systems has become a trend in a variety of fields, including military applications. Arduino as a microcontroller platform has attracted much attention due to its flexibility, availability, and affordability. The firing system is one of the important parts of weapons and ammunition that controls the launch of bullets or projectiles. The research is aimed at developing a mechanism for a remote-controllable fire system using radio frequency. The research uses several main components, including the Arduino Mega 2560, the TFT LCD ILI9486, and the radio-frequency module Digi XTend 900, electronic firing control and 38mm ammunition. The output of this research is a firing system that can be controlled remotely using a 38mm caliber ammunition with two shooting modes: single mode and salvo mode.